Spheres of influence in international relations history, theory and politics - Hast, Susanna (Routledge Ashgate, 2014)
Current events happening around the world, especially the 'humanitarian interventions' by NATO and the West within the context of the so-called Arab Spring, make the understanding of the role of spheres of influence in international politics absolutely critical. Hast explores the practical implications and applications of this theory.